Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Test - Page 578: 21



Work Step by Step

Given: $\sqrt {2x-3}=x-3$ Take square on both sides. we have, $(\sqrt {2x-3})^2=(x-3)^2$ or, $2x-3=x^2-6x+9$ or, $x^2-8x+12=0$ Factoization as follows: $(x-6)(x-2)=0$ or, $x=6,2$ Plug $x=6$ in the expression $\sqrt {2x-3}=x-3 \implies \sqrt {2(6)-3}=6-3 \implies 3 =3 $, we get the value of $x=6$ satisfies the expression.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.